The impact of maritime trade disruptions on food security: the case of imported calories - Tilford, Jenae Noelle (My University, 2025)
World trade is heavily dependent on maritime travel of goods and services (Brancaccio, et al. 2020; UNCTAD, 2024; Wang, et al., 2024). Key maritime passageways, such as the Panama Canal, the Strait of Gibraltar, the Turkish Straits, the Suez Canal, and the Strait of Malacca, facilitate global shipping but often face heavy congestion (Bailey and Wellesley, 2017). More than fifty five percent of internationally traded maize, wheat, rice, and soybeans are shipped through at least one maritime chokepoint (Bailey and Wellesley, 2017). Within recent years, there has been an increasing number of global supply chain disruptions that have grown in magnitude and frequency straining trade routes and impacting food availability and prices. This paper evaluates which countries face the greatest risks to their food supplies when ships can no longer utilize the Panama Canal, the Suez Canal, or the Malacca Strait due to temporary disruptions. The empirical strategy is to elicit country-by-country changes in imports of calories embodied in maize, wheat, and rice when one of the focus chokepoints experiences a disruption. To do this, the gravity model effectively captures changes in trade between countries (Head and Mayer, 2014; Pfaffermayr, 2023; Yotov, et al., 2016). The analysis uses bilateral trade data from FAOSTAT and is converted to calories using conversion factors, also from FAO. Dyadic covariates (e.g., trade agreements) are provided by the USITC Gravity Portal Trade and Production Database and the CEPII Gravity Database, and coordinates of major ports in each country are sourced from the World Port Index of the Geospatial-Intelligence Agency (2019). The coordinates are used as inputs in the maritime routing tool Searoute (Gaffuri 2024) which computes the shortest maritime route following the path of the most used shipping routes published in the Oak Ridge National Labs’ Global Shipping Lane Network (2000). One gravity model was constructed and used to evaluate four scenarios. One baseline and three counterfactuals reflecting the absence of specific chokepoints. The gravity models are fitted with data for the years 2010-2022. The results show for every 1% increase in distance between two countries, leads to a 1.19% decrease in imported calories for the receiving country. Among the countries included in this analysis, El Salvador experienced the largest change in imported calories when the Panama Canal was unavailable, with a 62.00% decrease. When the Suez Canal was inaccessible, Jordan saw an 81.36% reduction in imported calories. The removal of the Malacca Strait from shipping routes resulted in a 19.87% decrease in imported calories for Malaysia. While this paper solely focuses on a few specific maritime chokepoints, there are many other chokepoints along the agricultural and food supply chains that prevent countries from having open access to food---thus the analysis provides a building stone for more complex analysis. More generally, this analysis sheds light on the importance and need of collaboration amongst international countries and governments to protect these chokepoints and reduce pressure on these critical trade routes.
Keywords: Maritime; Trade disruptions; Food security; Gravity trade model